Pathophysiology of intestinal metaplasia of the stomach: emphasis on CDX2 regulation. (22nd March 2010) - Barros, Rita; Camilo, Vânia; Pereira, Bruno; Freund, Jean-Noel; David, Leonor; Almeida, Raquel
Abstract : IM (intestinal metaplasia) of the stomach is a pre-neoplastic lesion that usually follows Helicobacter pylori infection and that confers increased risk for gastric cancer development. After setting the role played by CDX2 ( Caudal -type homeobox 2) in the establishment of gastric IM, it became of foremost importance to unravel the regulatory mechanisms behind its de novo expression in the stomach. In the present paper, we review the basic pathology of gastric IM as well as the current knowledge on molecular pathways involved in CDX2 regulation in the gastric context.